Communication as a Strategy for Implementing the Language-in-Education Policy in Botswana Primary Schools - Mokibelo, Eureka (Advances in Social Sciences Research Journal, 2017)
This paper examines the role that communication plays as a strategy for implementing the language-in-education policy (LiEP) by teachers, school management and education officers in Botswana primary schools. Communication is at the pinnacle of the implementation of the language-in-education policy. This is confirmed by the diffusion of innovation and the eagle leadership theories. If ignored, it could lead to frustration and despair amongst policy agents. This study adopted the qualitative approach with open ended questionnaires, interviews and classroom observations techniques to investigate the problem. The findings indicate that effective communication was lacking in the implementation process of the language-in-education policy and this has led to disconnectedness, detachment, burn out and frustration amongst teachers. In the light of these findings, this study suggested the development of leadership and management in education officers, school management and teachers to raise their awareness about the critical role they can play in successfully implementing the LiEP through diverse communication channels. This study concluded that there should be, a reflection and change of behaviour by both senior personnel and teachers in primary schools to achieve the objectives of the language-in-education policy.